Consuming Costly Prey: Optimal Foraging and the Role of Compensatory Growth - Langerhans, Randall Brian; Goins, Taylor R.; Stemp, Kenzi M.; Riesch, Rüdiger; Araújo, Márcio S.; Layman, Craig A. (Frontiers in Ecology and Evolution, 2021)
Some prey are exceptionally difficult to digest, and yet even non-specialized animals may consume them—why? Durophagy, the consumption of hard-shelled prey, is thought to require special adaptations for crushing or digesting the hard shells to avoid the many potential costs of this prey type. But many animals lacking specializations nevertheless include hard-bodied prey in their diets. We describe several non-mutually exclusive adaptive mechanisms that could explain such a pattern, and point to optimal foraging and compensatory growth as potentially having widespread importance in explaining costly-prey consumption. We first conducted a literature survey to quantify the regularity with which non-specialized teleost fishes consume hard-shelled prey: stomach-content data from 325 teleost fish species spanning 82 families (57,233 stomach samples) demonstrated that non-specialized species comprise approximately 75% of the total species exhibiting durophagy, commonly consuming hard-shelled prey at low to moderate levels (~10–40% as much as specialists). We then performed a non-invasive diet survey to assess the frequency of molluscivory across the native latitudinal range of a small livebearing fish, Gambusia holbrooki, lacking durophagy specializations. Molluscivory was regionally widespread, spanning their entire native latitudinal range (> 14° latitude). Third, we tested for a higher frequency of molluscivory under conditions of higher intraspecific resource competition in Bahamian mosquitofish (Gambusia spp.). Examining over 5,300 individuals, we found that molluscivory was more common in populations with higher population density, suggesting that food limitation is important in eliciting molluscivory. Finally, we experimentally tested in G. holbrooki whether molluscivory reduces growth rate and whether compensatory growth follows a period of molluscivory. We found that consumption of hard-shelled gastropods results in significantly reduced growth rate, but compensatory growth following prior snail consumption can quickly mitigate growth costs. Our results suggest that the widespread phenomenon of costly-prey consumption may be partially explained by its relative benefits when few alternative prey options exist, combined with compensatory growth that alleviates temporary costs.